A concise review of lobster utilization by worldwide human populations from prehistory to the modern era. (7th May 2015) - Spanier, Ehud; Lavalli, Kari L.; Goldstein, Jason S.; Groeneveld, Johan C.; Jordaan, Gareth L.; Jones, Clive M.; Phillips, Bruce F.; Bianchini, Marco L.; Kibler, Rebecca D.; Díaz, David; Mallol, Sandra; Goñi, Raquel; et al.
Abstract: Lobsters are important resources throughout the world's oceans, providing food security, employment, and a trading commodity. Whereas marine biologists generally focus on modern impacts of fisheries, here we explore the deep history of lobster exploitation by prehistorical humans and ancient civilizations, through the first half of the 20th century. Evidence of lobster use comprises midden remains, artwork, artefacts, writings about lobsters, and written sources describing the fishing practices of indigenous peoples. Evidence from archaeological dig sites is potentially biased because lobster shells are relatively thin and easily degraded in most midden soils; in some cases, they may have been used as fertilizer for crops instead of being dumped in middens. Lobsters were a valuable food and economic resource for early coastal peoples, and ancient Greek and Roman Mediterranean civilizations amassed considerable knowledge of their biology and fisheries. Before European contact, lobsters were utilized by indigenous societies in the Americas, southern Africa, Australia, and New Zealand at seemingly sustainable levels, even while other fish and molluscan species may have been overfished. All written records suggest that coastal lobster populations were dense, even in the presence of abundant and large groundfish predators, and that lobsters were much larger than at present. Lobsters gained a reputation as "food for the poor" in 17th and 18th century Europe and parts of North America, but became a fashionable seafood commodity during the mid-19th century. High demand led to intensified fishing effort with improved fishing gear and boats, and advances in preservation and long-distance transport. By the early 20th century, coastal stocks were overfished in many places and average lobster size was significantly reduced. With overfishing came attempts to regulate fisheries, which have varied over time and have met with limited success.